2018
DOI: 10.1002/brb3.1072
|View full text |Cite
|
Sign up to set email alerts
|

Weaker semantic language lateralization associated with better semantic language performance in healthy right‐handed children

Abstract: IntroductionThe relationship between language abilities and language lateralization in the developing brain is important for our understanding of the neural architecture of language development.MethodsWe investigated 35 right‐handed children and adolescents aged 7–16 years with a functional magnetic resonance imaging language paradigm and a comprehensive language and verbal memory examination.ResultsWe found that less lateralized language was significantly correlated with better language performance across are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 87 publications
3
19
0
Order By: Relevance
“…Previous literature in healthy children and adolescents found an association between language lateralization and functioning, but conflicting findings were reported regarding the nature of this relationship: some studies found a positive correlation between language lateralization towards the left hemisphere and verbal abilities, 43, 44 whereas others reported better language performance related to less lateralization and more involvement of the contralateral hemisphere. 29, 30, 4547 The contradictory findings of these studies may be the result of different imaging methods and different tasks testing different functions. The relationship between lateralization and cognitive functioning has been reported as dependent on task demands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature in healthy children and adolescents found an association between language lateralization and functioning, but conflicting findings were reported regarding the nature of this relationship: some studies found a positive correlation between language lateralization towards the left hemisphere and verbal abilities, 43, 44 whereas others reported better language performance related to less lateralization and more involvement of the contralateral hemisphere. 29, 30, 4547 The contradictory findings of these studies may be the result of different imaging methods and different tasks testing different functions. The relationship between lateralization and cognitive functioning has been reported as dependent on task demands.…”
Section: Discussionmentioning
confidence: 99%
“…During fMRI assessment, the German version of an auditory description definition task was administered (Bartha‐Doering, Kollndorfer, et al, 2018; Bartha‐Doering, Novak, et al, 2018; Berl et al., 2014; Sepeta et al., 2016). In the auditory description definition condition, the participants heard the definition of an object followed by a noun and were instructed to press a button each time the definition truly described the noun.…”
Section: Methodsmentioning
confidence: 99%
“…Each block lasted for 40 s and consisted of 10 sentences presented every 4 s. Total fMRI scan time was 6 min 40 s. Task performance was evaluated by the overall accuracy in the language condition and the control task separately. Detailed description of the fMRI paradigm can be found in Bartha‐Doering, Kollndorfer, et al (2018), Bartha‐Doering, Novak, et al (2018), or Bartha‐Doering et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
“…The network of the left IFG and the precuneus may be involved in the naive phonetic processing of Kanji (Williams et al, 2015 ). Further, bilateral frontal involvement with weak semantic language lateralization is associated with a higher vocabulary in healthy children (Bartha-Doering et al, 2018 ). The fronto-parietal top-down control network might support rapid adjustment of multiple processes of Kanji reading (Dosenbach et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%